Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2023
DOI: 10.1128/mbio.00358-23
|View full text |Cite
|
Sign up to set email alerts
|

Advances and Breakthroughs in IRES-Directed Translation and Replication of Picornaviruses

Abstract: The family Picornaviridae is divided into 68 genera and 158 species. The viruses belonging to this family range from public health importance, such as poliovirus, enterovirus A71, and hepatitis A virus, to animal viruses of great economic importance, such as foot-and-mouth disease virus.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 176 publications
0
12
0
Order By: Relevance
“…These results indicated that RALY represses the FMDV IRES-driven translation. To initiate IRES-driven translation, the highly conserved virus IRES structure recruits some canonical initiation factors and 40S sub-unit with high affinity, subsequently assembling an 80S ribosome for the translation of viral proteins ( 9 , 13 ). The 80S ribosome assembly on the IRES involves multiple steps manipulated by specific IRES structure domains.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These results indicated that RALY represses the FMDV IRES-driven translation. To initiate IRES-driven translation, the highly conserved virus IRES structure recruits some canonical initiation factors and 40S sub-unit with high affinity, subsequently assembling an 80S ribosome for the translation of viral proteins ( 9 , 13 ). The 80S ribosome assembly on the IRES involves multiple steps manipulated by specific IRES structure domains.…”
Section: Discussionmentioning
confidence: 99%
“…During ribosome complex recruitment, the core domain of IRES interacts with some canonical initiation factors and 40S sub-unit and then assembles an 80S ribosome to translate viral protein ( 12 ). Picornavirus IRES has been classified into five distinct types based on their use of ITAFs, eukaryotic initiation factors (eIFs), and the secondary structure of viral IRES sequence ( 13 ). The type II IRES of FMDV is one of the strongest IRESs and can quickly hijack the eIFs of host cells and initiate the translation of viral proteins ( 14 ).…”
Section: Introductionmentioning
confidence: 99%
“…As shown in Figure 1 , the 5” end of the genome is linked to VPg, which can be uridylated by the 3D pol protein to act as a primer for transcription [ 1 , 13 ]. The 5”-UTR contains the internal ribosome entry site (IRES), which directs the cap-independent initiation of protein synthesis [ 14 ]. The 3’-UTR has a stem-loop structure and polyA tail, which is essential for picornaviruses [ 15 ].…”
Section: Introductionmentioning
confidence: 99%
“…The 3’-UTR has a stem-loop structure and polyA tail, which is essential for picornaviruses [ 15 ]. All Picornaviridae members have a single ORF, which translates a polyprotein that is cleaved by the viral proteases 2A pro , 3C pro , and 3 CD pro into the precursor proteins P1, P2, and P3 [ 14 , 16 ]. The P1 precursor protein is then cleaved into four structural proteins, which we have designated VP1, VP2, VP3, and VP4; the P2 precursor protein is processed into nonstructural proteins 2A pro , 2B, and 2C; and the P3 precursor protein undergoes proteolytic cleavage into nonstructural proteins 3A, 3B, 3C pro , and 3D pol [ 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…Initiation of IRES-mediated translation occurs using only a subset of eIFs (as certain eIFs are degraded in order to inhibit host cap-dependent translation. The binding of ITAFs at specific regions of IRES can act as RNA chaperones and modulate IRES structure to make translation initiation feasible with the available subset of eIFs [ 27 , 28 ].…”
Section: Introductionmentioning
confidence: 99%